Effects of Sub-Chronic MPTP Exposure on Behavioral and Cognitive Performance and the Microbiome of Wild-Type and mGlu8 Knockout Female and Male Mice - Torres, Eileen Ruth S.; Akinyeke, Tunde; Stagaman, Keaton; Duvoisin, Robert M.; Meshul, Charles K.; Sharpton, Thomas J.; Raber, Jacob (Frontiers in Behavioral Neuroscience, 2018)
Motor dysfunction is a hallmark of Parkinson’s disease (PD); however, non-motor symptoms such as gastrointestinal dysfunction often arise prior to motor symptoms. Alterations in the gut microbiome have been proposed as the earliest event in PD pathogenesis. PD symptoms often demonstrate sex differences. Glutamatergic neurotransmission has long been linked to PD pathology. Metabotropic glutamate receptors (mGlu), a family of G protein-coupled receptors, are divided into three groups, with group III mGlu receptors mainly localized presynaptically where they can inhibit glutamate release in the CNS as well as in the gut. Additionally, the gut microbiome can communicate with the CNS via the gut-brain axis. Here, we assessed whether deficiency of metabotropic glutamate receptor 8 (mGlu8), group III mGlu, modulates the effects of the neurotoxin, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), on behavioral and cognitive performance in female and male mice. We studied whether these effects are associated with changes in striatal tyrosine hydroxylase (TH) levels and the gut microbiome. Two-week sub-chronic MPTP increased activity of female and male wild-type (WT) and mGlu8 knockout (KO) mice in the open field. MPTP also showed genotype- and sex-dependent effects. MPTP increased the time WT, but not KO, females and males spent exploring objects. In WT mice, MPTP improved sensorimotor function in males but impaired it in females. Further, MPTP impaired cued fear memory in WT, but not KO, male mice. MPTP reduced striatal TH levels in WT and KO mice but these effects were only pronounced in males. MPTP treatment and genotype affected the diversity of the gut microbiome. In addition, there were significant associations between microbiome α-diversity and sensorimotor performance, as well as microbiome composition and fear learning. These results indicate that specific taxa may directly affect motor and fear learning or that the same physiological effects that enhance both forms of learning also alter diversity of the gut microbiome. MPTP's effect on motor and cognitive performance may then be, at least in part, be mediated by the gut microbiome. These data also support mGlu8 as novel therapeutic target for PD and highlight the importance of including both sexes in preclinical studies.